2018
DOI: 10.5144/0256-4947.2018.427
|View full text |Cite
|
Sign up to set email alerts
|

Demographic features of patients with colorectal carcinoma based on 14 years of experience at Jordan University Hospital

Abstract: BACKGROUNDColorectal cancer (CRC) is the third most common cancer worldwide. In the West, the incidence has stabilized or decreased. There are only occasional published studies that describe the epidemiology of CRC and its changing trends in Jordan and other Middle Eastern countries.OBJECTIVESDescribe the epidemiological features of CRC, predict future trends and compare the results with those from other Arab and Middle Eastern countries and the West.DESIGNRetrospective epidemiologic study.SETTINGTertiary cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…In addition, during this period, CIR per 100,000 increased across all time periods for both males (14.4, 16.8, and 21.9) and females (11.4, 10.7, and 13.7). These results are consistent with those of an earlier study reporting that the incidence of CRC was higher among males and that sex differences were the highest in the population aged ≥65 years 14 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, during this period, CIR per 100,000 increased across all time periods for both males (14.4, 16.8, and 21.9) and females (11.4, 10.7, and 13.7). These results are consistent with those of an earlier study reporting that the incidence of CRC was higher among males and that sex differences were the highest in the population aged ≥65 years 14 .…”
Section: Discussionsupporting
confidence: 93%
“…Majority of studies of CRC in Arab countries found that the most affected site is the rectum, followed by sigmoid and distal colon. This is similar to reports from western and regional countries [7,9,[11][12][13][14][15][16][17]. In fact, there is a noticeable shift toward proximal colon cancer in western countries which has been explained by the high success rate of CRC screening for detection of rectal and distal colon tumors, leaving the proximal colon cancer undetected till late in the disease [1,18,19].…”
Section: Lateralizationsupporting
confidence: 87%
“…From table 23.1, Comoros reported the least CRC Age-Standardized Rate (ASR) (4.5/100,000) of both genders among Arab countries, while Gaza Strip reported the maximum ASR (18.6/100,000). It is very noticeable from the GLOBOCAN report that there is a multi-fold increase in the ASR in this region compared to previously reported ASR in the region [4,[6][7][8][9].…”
mentioning
confidence: 55%
See 2 more Smart Citations